2018
DOI: 10.1038/s41398-018-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain monoamine oxidase A in seasonal affective disorder and treatment with bright light therapy

Abstract: Increased cerebral monoamine oxidase A (MAO-A) levels have been shown in non-seasonal depression using positron emission tomography (PET). Seasonal affective disorder (SAD) is a sub-form of major depressive disorder and is typically treated with bright light therapy (BLT). The serotonergic system is affected by season and light. Hence, this study aims to assess the relevance of brain MAO-A levels to the pathophysiology and treatment of SAD. Changes to cerebral MAO-A distribution (1) in SAD in comparison to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 41 publications
1
39
1
Order By: Relevance
“…Light therapy has been well accepted for the treatment of depression. In recent years, studies using [ 11 C]harmine, [ 11 C]DASB, and [ 18 F]FDG PET proved that light therapy can modulate the levels of MAO-A, 5-HTT, and glucose metabolism in the brain of depression patients 6,7,48 . On the one hand, these studies provided useful information for understanding light therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light therapy has been well accepted for the treatment of depression. In recent years, studies using [ 11 C]harmine, [ 11 C]DASB, and [ 18 F]FDG PET proved that light therapy can modulate the levels of MAO-A, 5-HTT, and glucose metabolism in the brain of depression patients 6,7,48 . On the one hand, these studies provided useful information for understanding light therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) is a well-recognized imaging method for noninvasive diagnosis and efficacy evaluation of neuropsychiatric disorders, besides, PET combined with specific radiotracers has great benefits for revealing pathogenesis and developing therapeutics. For example, recent studies demonstrated the reduced cerebral MAO-A levels and serotonin transporter binding potential in patients with depression after a few weeks of bright light therapy using [ 11 C]harmine and [ 11 C]DASB PET imaging 6,7 . However, the complex pathology of depression makes it still possesses many other important targets worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with seasonal affective disorders (SADs) have higher SERT levels compared with healthy control subjects only in winter ( Nørgaard et al, 2017 ), while light therapy leads to reduced SERT availability in patients with SADs ( Tyrer et al, 2016 ). Monoamine oxidase A density in healthy humans ( Spies et al, 2018 ) and striatal dopamine synthesis in patients with Parkinson's disease ( Kaasinen et al, 2012 ) are also higher in fall and winter compared with spring and summer. Therefore, evidence on PET studies suggests seasonality effects on the brain across multiple neurotransmitter systems, and this is potentially driven by interactions between the specific systems ( Tuominen et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, illness severity seems to be a crucial factor regarding the reported elevation of cerebral MAO-A density which could not be observed in previously investigated mildly to moderately depressed patients, even when unmedicated [35,36]. Here, we included only patients with a HAMD 17 greater than 23 referred to the department for the administration of ECT and fulfilling criteria for treatment-resistance [3,40,43]. TRD is associated with distinct sociodemographic, clinical and biological risk factors that are not necessarily associated with non-treatmentresistant depression [4,5,58e61] which might equally contribute to the fact that we could not ascertain the findings published by Meyer et al [30].…”
Section: Discussionmentioning
confidence: 99%
“…Seven healthy subjects with compatible inclusion criteria had participated in an earlier PET study using [ 11 C]harmine at the Department of Psychiatry and Psychotherapy of the Medical University of Vienna (Austrian Science Fund, FWF P24359) [43] and the available image data were used (identical PET protocol, same PET scanner). PET measurements of healthy individuals had to be performed during the same season (fall/winter or spring/summer) as patients to rule out seasonal variations of MAO-A V T which have been shown previously by our group [43]. Subjects had to be physically healthy, non-smoking and without any history of previous mental disorder or treatment with psychotropic medication.…”
Section: Subjects and Study Designmentioning
confidence: 99%